FePt electrodeposited from ionic liquids on Si(111) substrate. (3rd May 2016) - Wei, G.; Zhou, H.; Ge, H.; Dettinger, H.
Abstract : This work concerns FePt nanowires electrodeposited from electrolyte of E1 [ammonium hexachloroplatinate (25 mM L − 1 ), 1-ethyl-3-methylimidazolium chloride (25 mM L − 1 )], iron dichloride (315 mM L − 1 ) and glycol (50 mL) at 393 K. FePt nanowires and films were electrodeposited by controlling the electrodeposited time under suitable potential in E1. FePt nanowires were prepared at different times of 600, 800 and 1000 s when deposition potential was − 2·0 V versus Ag/AgCl. The SEM patterns proved that FePt nanowires were prepared at suitable deposition time (600–1000 s). The X-ray diffraction pattern indicated that the face centre tetragonal structure of FePt nanowires was obtained. Magnetic hysteresis loops showed that aggregation could decrease the coercivity, and some nanowires were larger than the mean diameter, which exhibited a comparatively large ferromagnetic behaviour.